UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN SIKAP JUJUR SISWA DI SEKOLAH MENENGAH KEJURUAN ISLAM TERPADU RABBI RADHIYYAH CAWANG BARU - Siswanto -; Asori - (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2018)
This research is motivated by the number of cheating behaviors in teaching and learningactivities including in making homework assignments, daily assessments, and semesterassessments. Thus a teacher must have efforts or ways to anticipate fraud committedby his students. Because in terms of religion reflects bad character. For this reason RRCawang Baru IT Vocational School needs to instill an honest attitude to its students, byinstilling or correcting honesty with students from now on, we will improve the honestyof the nation in the future. This study aims to find out: 1) What is the effort of Islamicreligious education teachers in instilling honesty in the learning process in Cawang BaruRR IT Vocational School? 2) What are the efforts of Islamic religious education teachers ininstilling honesty outside the learning process in Cawang Baru RR IT Vocational School?3) What are the inhibiting factors in planting honest attitudes of students in CawangBaru RR IT Vocational School ?. The study aims to see how far the teacher instills honestattitudes of students inside and outside the learning process and the inhibiting factors ofplanting honest attitudes in the subjects of Islamic Education in the Cawang Baru RRVocational School, so that fraud can be overcome, and to achieve the purpose above, usedqualitative research methods with descriptive qualitative approaches, data collectiontechniques used were observation, interviews, and documentation. Data is analyzed, byreducing data, describing data and drawing conclusions. The results of the research thathave been investigated are that the planting of honest attitudes through the subjects ofIslamic Religious Education at Cawang Baru RR Vocational High School is as follows.The results of the first formulation are that the teacher instills honest attitudes by usingspies in the class that are trusted, and honesty can be justified, and by training studentsto fast Monday Thursday. Then the method of lecture, discussion, advice, stories andexamples and the results of their achievements from planting honest attitudes studentscan accept and practice the honest attitude that has been given by the teacher. In the thirdformulation of the problem is the inhibiting factor, they are not able to check studentsat all times, because of their limitations, because they are still one day not yet boardingschool so it is difficult for them to monitor the honesty of students when not in school andalso aspects of the student's environment itself starting from the aspect of his friend.